Algae Bioactive Constituents and Possible Role During COVID-19 Pandemic (A review) - Rashad, Sayed; El-Chaghaby, Ghadir (Iraqi Journal of Pharmaceutical Sciences, 2021)
Nowadays, the use of natural bio-products in pharmaceuticals is gaining popularity as safe alternatives to chemicals and synthetic drugs. Algal products are offering a pure, healthy and sustainable choice for pharmaceutical applications. Algae are photosynthetic microorganisms that can survive in different environmental conditions. Algae have many outstanding properties that make them excellent candidate for use in therapeutics. Algae grow in fresh and marine waters and produce in their cells a wide range of biologically active chemical compounds. These bioactive compounds are offering a great source of highly economic bio-products. The present review discusses the phytochemical and bioactive compounds present in algae biomass and their potent biological activities. The review focuses on the use of alga in therapy and their pharmaceutical applications with special reference to the possible preventive and therapeutic role of algae against COVID-19.